Intramuscular Injection of Follicle Stimulating Hormone on the Superovulation Response in Friesian Holstein and Ongole Grade Cattle - Dwiyoga, Irham Jodhi; Atabany, Afton; Komala, Iyep; Rosmayanti, Anni (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
Considering the limited availability of superior livestock seeds in Indonesia, using superovulation methods, which involve follicle-stimulating hormones to accelerate follicle development and increase ovulation, can solve embryo transfer processes. This study aims to analyze the superovulation response in Friesian Holstein (FH) and Ongole Grade (OG) cattle based on the number of corpus luteum (CL), collected embryos, viable embryos (VEs), non-viable embryos (NVEs), and the proportions of VEs and NVEs, categorized by age. The research was conducted at the Cipelang Embryo Center, involving 49 FH and OG cows, with synchronization, superovulation, embryo collection, and evaluation. Data were analyzed using an independent T-test in IBM SPSS Statistics. The results showed no differences between OG and FH cattle regarding CL count, embryo collection, and embryo quality. OG cattle had a higher CL count and embryo collection but also a larger proportion of degenerate embryos, indicating reproductive quality differences between these cattle breeds. This study highlights the importance of understanding genetic and age-based reproductive dynamics in livestock reproduction strategies, offering new insights into breeding techniques to improve the efficiency of superior livestock production in Indonesia.